IMPLEMENTASI KONSELING KREATIF PADA USIA REMAJA: SEBUAH TINJAUAN LITERATUR [IMPLEMENTATION OF CREATIVE COUNSELING ON YOUTH: A LITERATURE REVIEW] - Kurniasih, Anggita Fajar; Santosa, Hardi; Sumiyem, S (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
During adolescence, a person experiences a transition period with changes in psychosocial, emotional, physical, and behavior. This is what causes adolescents to experience several problems in personal, career, social, and study aspects. One effort to help the problems experienced by adolescents is to provide creative counseling services provided by counselors. The purpose of this research is to describe the implementation of creative counseling in adolescents. The research method used is library research. The results of the study indicate that there are three premises for the implementation of creative counseling in adolescents, namely: (1) providing space for counselors to develop their creativity in counseling; (2) creative counseling helps counselees to express problems more easily; and (3) helping counselors and counselees examine a problem from various aspects. The implementation of creative counseling should be utilized by counselors in designing effective counseling programs by increasing the success of counseling services in helping counselees overcome the problems they face.